2000
DOI: 10.1038/sj.ejcn.1600903
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary trans α-linolenic acid on plasma lipids and platelet fatty acid composition: the TransLinE study

Abstract: ; on behalf of the investigators of the TransLineE project { Objective: To collect (i) baseline data and (ii) execute a large multicentre study examining the effect of trans a-linolenic acid on its incorporation into plasma lipids and on risk factors for coronary heart disease. Design: Male volunteers were recruited and the habitual diet assessed by a 4-d weighed record. Fatty acid composition of plasma and platelet lipids were determined by gas chromatography at baseline. After a 6 week run-in period on a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 34 publications
(37 reference statements)
2
35
0
1
Order By: Relevance
“…Trans fatty acids compete with the essential fatty acids for the enzyme systems involved in these reactions. [38][39][40][41][42][43][44] With regard to the immune system, the splenic production of prostaglandin E 2 was reduced, while both plasma IgG and CD 4 + :CD 8 + T-lymphocytes ratio were increased by dietary trans fatty acids.…”
Section: Other Risks Of Trans Fatty Acidsmentioning
confidence: 99%
“…Trans fatty acids compete with the essential fatty acids for the enzyme systems involved in these reactions. [38][39][40][41][42][43][44] With regard to the immune system, the splenic production of prostaglandin E 2 was reduced, while both plasma IgG and CD 4 + :CD 8 + T-lymphocytes ratio were increased by dietary trans fatty acids.…”
Section: Other Risks Of Trans Fatty Acidsmentioning
confidence: 99%
“…21,23 The association between dietary TFAs and risk for CHD has strongly been suggested in many studies. [24][25][26][27][28] Willet et al reported that consumption of TFAs generated by partially hydrogenated vegetable oils including margarine indicated significant correlation with CHD onset. 29 Hu et al demonstrated that replacing saturated and TFAs with unhydrogenated monounsaturated and polyunsaturated fats is more effective in preventing CHD in women than reducing overall fat intake.…”
Section: Effects Of Tfa Intake On Risk Factors For Metabolic and Cardmentioning
confidence: 99%
“…Based on a few US food samples (e.g., mayonnaise, white bread, muffins), we crudely estimated the ratio of trans ALA to cis ALA was 1:7.5. By assuming that this ratio is generalizable to other trans ALA-containing foods, this translates into an intake of 0.2 g trans ALA/d on the basis of a mean intake of 1.5 g ALA/d in the US population (17), which is slightly lower but in the same magnitude as the estimated intake among Dutch and Scottish (0.5-0.7 g/d) and French participants (0.2-0.4 g/d) (24). Our study and the European study (24) both suggested a low concentration of erythrocyte trans ALA (w0.05% of total fatty acids) under a habitual diet.…”
Section: Discussionmentioning
confidence: 95%
“…Up to 40% of ALA can be present as trans isomers (19,20). trans ALA also occurs in human serum (24) and maternal milk (25,26).…”
Section: Introductionmentioning
confidence: 99%